Collections held by the Northumberland Record Office relating to Australia, New Zealand and the Pacific (as filmed by the AJCP) [M1652] - Australian Joint Copying Project; National Library of Australia; State Library of New South Wales; Northumberland Record Office; William Armstrong and Sons. (Canberra : Australian Joint Copying Project, 1950)
1. F.J. Brooks autograph collection, 1766-1891; 2. Middleton (Belsay) manuscripts, 1812-1824 containing papers of the Middleton family of Belsay Castle, Northumberland. 3. Papers of the Ridley family of Blagdon, Northumberland, 1822-1948. 4. Papers of the Blackett-Ord family of Whitfield Hall, Northumberland, 1822-1843. 5. Records of William Armstrong and Sons, consulting mining engineers of Newcastle upon Tyne, 1875-1885. 6. Journal of A. McCracken, 1849 Jan. 4-Apr. 24 on a voyage on the William Hyde to Australia. 7. Newcastle Diocesan Centenary records, 1982 re the Goodwill Mission from Newcastle, Australia to Newcastle upon Tyne.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the State Library of New South Wales.
National Library of Australia holds microfilm master.
Australian Joint Copying Project miscellaneous series M1652.
Also available online
Microfilm copy of originals held by Northumberland Record Office, Newcastle upon Tyne.
Descriptive list available (8 p.).
Keywords: William Armstrong and Sons -- Archives; Autographs -- Great Britain